Pengaruh Literasi Keuangan dalam Pengelolaan Keuangan: Menguji Efek Pendapatan Sebagai Moderasi - Rengga Madya Pranata; Asep Jamaludin; Ery Rosmawati; Aditya Duta Pangestu; Berliana Ananda Kutaningtyas (Lembaga Pengembangan Kinerja Dosen, 2024)
Financial management is a key aspect in achieving financial well-being of the community. However, the level of financial literacy in Indonesia is still low, requiring education and development of financial literacy to reduce ineffective financial decisions. The Financial Services Authority (OJK) and Universitas Gadjah Mada (UGM) are actively encouraging the improvement of financial literacy, with a focus on education, national campaigns, strengthening infrastructure, and developing affordable financial service products. Financial literacy, which includes knowledge, understanding, skills, and motivation in making financial decisions, has a positive impact on financial management behavior. Individuals with higher levels of financial literacy tend to make better financial decisions, avoid investment fraud, and understand the principles of financial planning. However, income also plays an important role as a moderator, influencing the relationship between financial literacy and financial management. Individuals with low incomes tend to have lower financial literacy, which can affect their financial management practices. Therefore, challenges such as behavioral bias and external factors can affect financial literacy and its management implementation.